Estimation of the economic value of surf tourism in Aljezur, Algarve, Portugal. An exploratory study. - Carrasco, P.; Contreiras, J. P.; Machado, V.; Duarte, A.P. (9th International Conference on Tourism (ICOT), 2019)
At the request of the City Council of Aljezur, Algarve, Portugal, in January 2015 to the University of Algarve (UALG) the authors began an exploratory study with a duration of one year, on the reality of the surf tourism product in the county. The objectives of this study were to monitor and study the tourism activity related to surfing in order to estimate the economic value generated directly by this activity. In addition, the obtained data that allowed the authors to draw a realistic and coherent scenario for the evolution of this surfing activity in a sustainable context and as a support product of nature tourism. 31 Surf schools operating in the municipality were identified and surveyed as the business entities that organize the surfing economic product. This survey allowed to collect the average expenses in terms of accommodation, travel, food and training in a total of 321 surfers inquired. At the same time, surfers were counted during a year of activity using local photos, beach webcams and face-to-face counting in each of the county beaches, complementing the information obtained through the questionnaires. This article is a result of the partial presentation of this study. Focusing mainly on the economic dimension, a matrix of characterization of the profile of the surfer and his economic contributions is presented, estimating a global value for the surfing activity in the municipality associated with two groups of surfers as well as with the activity of the schools of surf. Finally, a framework of generic and specific guidelines and strategies set out in the final study.